Nurturing Belonging, Reflection, and Responsiveness in Cross-Sector Partnerships: Exemplar From Community-Based Smart Health System Research - Connie K. Y. Nguyen-Truong; Roschelle L. Fritz; Jieheng Xu; Christine Lau; Holden Leung; Kit Kuran; Thai Hien Nguyen; Cang Le; Elke Li; Chenya Chiu; Maria Park; Nhu Le; et al. (Journal of Participatory Research Methods)
The National Academies of Sciences, Engineering, and Medicine emphasizes the need for research about belonging so work across systems and sectors can more effectively address antiracism. The purpose of this article is to share insights regarding how we successfully co-developed safe and equitable co-learning between cross-sector partners and how this led to a sustainable partnership. The purpose for cross-sector partnering was to work together to prepare for the Community-Based Smart Health System (SHS) community-based participatory research (CBPR) initiative. The SHS CBPR addresses advancing health equity and health technology (techquity) among community dwelling older adults to detect early changes in chronic health conditions using real-time sensor-based monitoring in the home. The cross-sector partnership consisted of a public academic university, a non-profit Asian-based community health and service center, a government administration affordable housing authority organization, and a non-profit faith-based free healthcare clinic. Partners engaged in relationship work together to nurture a sense of belonging, reflection, and responsiveness while preparing to work together on the SHS CBPR initiative towards optimal health and well-being for all. Preparatory work included three participatory methodological processes: (I) adapting the Community Cultural Wealth Framework from a strength-based lens as a guide, including acknowledging that racism is a daily risk factor and knowing and using strengths can protect against racism; (II) co-developing cross-sector partnership agreements that included statements regarding the co-construction of a safe and brave space; and (III) infusing partners’ voices into the co-design and other preparatory documents. In this article, we share insights about having exchanged knowledge and shared power in decision-making using authentic reflection that honored partners’ perspectives and demonstrated responsiveness to challenges. We describe necessary actions taken to mitigate a power differential. We end with suggestions for how researchers and partnerships can learn from our experience to enhance future initiatives to nurture a sense of belonging within their partnerships, especially partnerships involving testing or using new smart health technologies and automated remote health monitoring.